Tío & Tío : the ring bearers : based on a true story - García-Mathews, Wellinthon; Mathews, Ross, 1979- (Penguin Workshop, an imprint of Penguin Random House LLC, 2025)
Evan and Andy, excited for their uncles' wedding in Mexico, embrace their role as ring bearers as they witness the love and joy of the celebration.